Profiles of risk: a qualitative study of injecting drug users in Tehran, Iran - Green Traci; Movaghar Afarin; Razzaghi Emran M; Khoshnood Kaveh (BMC, 2006)
Abstract Background In Iran, there are an estimated 200,000 injecting drug users (IDUs). Injecting drug use is a relatively new phenomenon for this country, where opium smoking was the predominant form of drug use for hundreds of years. As in many countries experiencing a rise in injecting drug use, HIV/AIDS in Iran is associated with the injection of drugs, accounting for transmission of more than two-thirds of HIV infections. This study aimed to: describe the range of characteristics of IDUs in Tehran, Iran's capital city; 2) examine the injecting-related HIV risk behaviors of IDUs, and 3) suggest necessary interventions to prevent HIV transmission among IDUs and their families and sex partners. Methods Using rapid assessment and response methods with a qualitative focus, six districts of Tehran were selected for study. A total of 81 key informants from different sectors and 154 IDUs were selected by purposeful, opportunistic and snowball sampling, then interviewed. Ethnographic observations were done for mapping and studying injecting-related HIV risk settings and behaviors. Modified content analysis methods were used to analyze the data and extract typologies of injecting drug users in Tehran. Results Evidence of injecting drug use and drug-related harm was found in 5 of 6 study districts. Several profiles of IDUs were identified: depending on their socioeconomic status and degree of stability, IDUs employed different injecting behaviors and syringe hygiene practices. The prevalence of sharing injection instruments ranged from 30-100%. Varied magnitudes of risk were evident among the identified IDU typologies in terms of syringe disinfection methods, level of HIV awareness, and personal hygiene exhibited. At the time of research, there were no active HIV prevention programs in existence in Tehran. Conclusion The recent rise of heroin injection in Iran is strongly associated with HIV risk. Sharing injection instruments is a common and complex behavior among Iranian IDUs. For each profile of IDU we identified, diverse and targeted interventions for decreasing sharing behavior and/or its harms are suggested. Some notable efforts to reduce the harm of injecting drug use in Iran have recently been accomplished, but further policies and action-oriented research for identification of effective preventive interventions are urgently needed.